Representation and processing of mass and count nouns: a review - Fieder, Nora; Nickels, Lyndsey; Biedermann, Britta (Frontiers in Psychology, 2014)
Comprehension and/or production of noun phrases and sentences requires the selection of lexical-syntactic attributes of nouns. These lexical-syntactic attributes include grammatical gender (masculine/feminine/neuter), number (singular/plural) and countability (mass/count). While there has been considerable discussion regarding gender and number, relatively little attention has focused on countability. Therefore, this article reviews empirical evidence for lexical-syntactic specification of nouns for countability. This includes evidence from studies of language production and comprehension with normal speakers and case studies which assess impairments of mass/count nouns in people with acquired brain damage. Current theories of language processing are reviewed and found to be lacking specification regarding countability. Subsequently, the theoretical implications of the empirical studies are discussed in the context of frameworks derived from these accounts of language production (Levelt, 1989; Levelt et al., 1999) and comprehension (Taler and Jarema, 2006). The review concludes that there is empirical support for specification of nouns for countability at a lexical-syntactic level.